Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/es8030193
|View full text |Cite
|
Sign up to set email alerts
|

Vegetated Buffer Strips Can Lead to Increased Release of Phosphorus to Waters: A Biogeochemical Assessment of the Mechanisms

Abstract: Establishing vegetated buffer strips (VBS) between cropland and watercourses is currently promoted as a principal control of diffuse pollution transport. However, we lackthe mechanistic understanding to evaluate P retention in VBS and predict risks of P transport to aquatic ecosystems. We observed that VBS establishment led to enhanced rates of soil P cycling, increasing soil P solubility and the potential amount leached to watercourses. Soil in VBS, relative to adjacentfields, had increased inorganic P solubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 32 publications
6
90
0
Order By: Relevance
“…For example, riparian and upland areas can be simulated. Because of the lateral connectivity between upland and riparian areas, representing watershed hydrology using a series of vertically stacked buckets may not be appropriate for simulating the hydrochemistry of headwater forest (Löfgren et al, 2011) or agricultural (Stutter et al, 2009) watersheds. When simulating laterally connected bucket systems used to represent riparian and upland areas, some additional parameters must be specified for the different buckets so as to ensure that hydrology is represented correctly.…”
Section: Hydrological Response (Landscape) Unit Typesmentioning
confidence: 99%
“…For example, riparian and upland areas can be simulated. Because of the lateral connectivity between upland and riparian areas, representing watershed hydrology using a series of vertically stacked buckets may not be appropriate for simulating the hydrochemistry of headwater forest (Löfgren et al, 2011) or agricultural (Stutter et al, 2009) watersheds. When simulating laterally connected bucket systems used to represent riparian and upland areas, some additional parameters must be specified for the different buckets so as to ensure that hydrology is represented correctly.…”
Section: Hydrological Response (Landscape) Unit Typesmentioning
confidence: 99%
“…According to the results, the arable land was main zone contributed significantly to P release during a water storage period, and 51.7% of the total newly submerged area in the Danjiangkou Reservoir was designated as arable land, thus it was important to explore the distribution characteristics of P in the arable land. Besides, it unwise to establish grass buffer strips in the newly submerged area, because grass buffer strips may be increasing the susceptibility P move to adjoining water (Stutter et al, 2009). …”
Section: 38%mentioning
confidence: 99%
“…diversity dynamics, species composition, food web structure, diversifying plant-microbial system, ecosystem stability/functioning, organic agriculture, biodiversity law, watershed ecosystem management, assessment of ecosystems and biodiversity, scale dependence) (Stutter et al, 2009;Shennan, 2008;Menalled et al, 2001, Bartels andChen, 2010;Crowder et al, 2010;Bai et al, 2004;Davis et al, 2007;Bernez et al, 2002;Marris, 2010;Crawley and Harral, 2001). For instance, Menalled et al (2001) suggested that agricultural management systems can have both immediate and long-term effects on weed species density, abundance and diversity.…”
Section: Applying General Model To Species Conservation and Ecosystemmentioning
confidence: 99%
“…Shennan (2008) proposed that important elements for understanding biotic interactions include consideration of the effects of diversity, species composition and food web structure on ecosystem processes; the impacts of timing, frequency and intensity of disturbance; and the importance of multitrophic interactions in agroecosystem. Stutter et al (2009) proposed a mechanism whereby the establishment of vegetated buffer strips between cropland and watercourses on previous agricultural land causes a diversifying plant-microbial system. Bartels and Chen (2010) explained that whether resource quantity or resource heterogeneity is the determinant of under-story plant diversity in individual studies was dependent on stand succession stage(s), presence or absence of intermediate disturbance, and forest biome within which the studies were conducted.…”
Section: Applying General Model To Species Conservation and Ecosystemmentioning
confidence: 99%